ANALISIS HUKUM TERHADAP PENANGANAN PIRACY JURE GENTIUM DAN ARMED ROBBERY DI WILAYAH LAUT (Kajian Terhadap Penanganan Piracy Jure Gentium dan Armed Robbery di Selat Malaka-Singapura dan di Perairan Somalia) - , GERALD ALDITYA BUNGA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is proposed to answer the problems in this research. Firstly, why need the clear legal determination on the distinction between piracy jure gentium and armed robbery. Secondly, how the handling of piracy jure gentium and armed robbery conducted at sea outside the territorial sea and the waters of Somalia and the Strait of Malacca and Singapore. This research is normative research thus the research methods used here is the normative research method. This research examined the arrangements on piracy jure gentium and armed robbery. This research also compared the handling of piracy jure gentium and armed robbery at sea outside the territorial sea and the waters of Somalia and the Strait of Malacca and Singapore. The results of this research indicates that piracy jure gentium and armed robbery are two different issues and should be regulated differently, but currently there is no international rules that applies globally governing the issue of armed robbery. UNCLOS 1982 as the international maritime law applicable globally regulates only the issue of piracy jure gentium. Regional Cooperation Agreement on Combating Armed Robbery against Ships in Asia and IMO Resolution A.922(22) Code of Practice for the Investigation of the Crimes of Piracy and Armed Robbery against Ships regulate the issue of armed robbery, but ReCAAP is binding only several states and and IMO Resolution A.922(22) Code of Practice for the Investigation of the Crimes of Piracy and Armed Robbery against Ships is formed in soft law form. The way to overcome piracy jure gentium and armed robbery in Somalia can not be applied in the Strait of Malacca and Singapore, as Indonesia, Malaysia, and Singapore have the capacity to secure the area, and in the Straits of Malacca and Singapore there is no high seas thus the handling of armed robbery in that area subject to the jurisdiction of Indonesia, Malaysia, and Singapore. In each of the UN Security Council resolution on handling the act piracy jure gentium and armed robbery at sea outside the territorial waters of Somalia also expressed that what is implemented in Somalia is only applied to related to the crisis in Somalia and not become a customary international law.